Development of biosensor systems for the detection of anti-cancer drugs and prostate cancer - Mwanza, Daniel (Rhodes University, Faculty of Science, Department of Chemistry)
Rapid, low-cost and accurate point-of-care analytical devices are highly required for the detection of cancer biomarkers for the early diagnosis and determination of anti-cancer drugs for monitoring of cancer-related diseases. This thesis focused on the development of biosensor systems for the detection of anti-cancer drug, methotrexate (MTX) and prostate cancer biomarker, prostate-specific antigen (PSA). Ultrasensitive electrochemical immunosensors were fabricated by covalent immobilization of polyclonal anti-MTX and monoclonal anti-PSA antibodies onto glassy carbon, screen-printed carbon and gold electrodes which were pre-modified with isophthalic acid (IPA) thin monolayer film. A methodology based on the steric hindrance by 1,3-substituted aryldiazonium salt was adopted to enable the electrografting of IPA thin monolayer film on electrode surfaces. The antibodies were immobilized onto the IPA thin monolayer film via carbodiimide chemistry to form a sensing or analyte capture surface. For the detection of MTX, the analytical performance of the non-Faradaic electrochemical impedance spectroscopy (EIS) immunosensor was validated using singular value decomposition (SVD). The non-Faradaic EIS detection of PSA was validated using Nyquist plots of total capacitance, complex capacitance calculated from the imaginary part of impedance, and the capacitance acquired from the circuit fitting. The detection of PSA was further studied using colorimetric sensing platform which was developed by forming a sandwich immunoassay. For the immunoassay detection, the anti-PSA captured monoclonal antibodies were immobilized onto the microwell plates. The sensing signal was obtained from bioconjugating the anti-PSA antibody polyclonal onto glucose-encapsulating nanoliposomes (GENLs-anti-PSA-pAb). The preparation of glucose -encapsulated nanoliposomes were evaluated for their potential to release glucose in a controlled manner using Triton-X 100 or acidic phosphate buffer saline (PBS, pH 5.0). The detection of PSA (in a sandwich manner) was correlated to the concentration of glucose quantified using horseradish peroxidase (HRP), Pd

PdO nanoparticles, and personal glucose meter. The immunosensors developed in this work exhibited high stability, selectivity, low detection limits, and a wide linear range which was suitable for screening of both PSA and MTX.
Keywords: Prostate Cancer; Cancer -- Treatment; Cancer -- Early detection; Biosensors; Methotrexate; Prostate-specific antigen